Technology Adoption and Reduction of Social Inequalities - Arif, Muhammad (Journal of Global Social Transformation, 2025)
The adoption of technology has become one of the potent factors to resolve the social inequalities in the sectors of education, healthcare and economy. New technologies, mobile platform, digital education tools, telemedicine, and information communication technologies (ICTs), could close access disparities and enhance opportunities and lead to a higher degree of social inclusion. Nevertheless, infrastructure disparities, affordability, digital awareness and awareness in the mainstream culture are significant obstacles to equal technology adoption. This paper explores ethical problems inherent in the implementation of technology to bridge social inequalities on the basis of social-economic, cultural and policy, and the assessment of applications that can be put into use by the developing economies. Based on the systematic review and synthesis of the empirical research, the research identifies the opportunities, as well as limitations that are centered on the strategies of inclusive and socially equitable technology implementation.
Keywords: Adoption of technology; Social inequality; digital divide; notion of digital literacy; socio-economic development; ICT; inclusion; emerging economies